Hubungan Health Literacy dengan Pola Makan dan Kepatuhan Minum Obat Pasien Hipertensi - Ekawati Ekawati; Ahmad Ikhlasul Amal; Retno Setyawati (PPNI UNIMMAN, 2026)
Hypertension is a condition characterized by systolic blood pressure ≥140 mmHg and diastolic blood pressure ≥90 mmHg. In Indonesia, the prevalence of hypertension showed an increasing trend in 2018, reaching 34.1% based on national survey data. Effective control of hypertension is essential to prevent long-term complications and acute cardiovascular events. Non-adherence to antihypertensive medication can increase cardiac workload. In addition to adherence to pharmacological therapy, unhealthy dietary patterns also contribute to the rising prevalence of hypertension. Therefore, adequate health literacy is required to support patients with hypertension in maintaining regular medication use and adopting healthy lifestyle changes, particularly in dietary management. To determine the relationship between health literacy and dietary patterns, as well as medication adherence among patients with hypertension. This study employed a non-experimental descriptive analytic design with a cross-sectional approach involving 113 respondents. Data were collected using questionnaires with ordinal scales and analyzed using the Gamma test. The results showed a p-value of 0.00 (<0.05) with correlation coefficients of R = 0.982 and R = 1.000, indicating a positive and very strong relationship between health literacy and dietary patterns, as well as medication adherence. There is a positive and very strong relationship between health literacy and dietary patterns and medication adherence among patients with hypertension.